Construction of the Cuban identity and its evolution in the socio-political system - L. V. Savin (Ибероамериканские тетради)
Interview with Elena Maria Diaz Gonzalez, Professor at the Latin American Faculty of Social Sciences (FLACSO). Academic career of Prof. Diaz Gonzalez focuses on social development in Latin America and divergences on public policy and gender. She has led numerous research teams, developing valuable materials on the history of Cuba, the dynamics reflecting Cuba’s importance in the international arena, and the recognized Cuban contribution to countries that require international humanitarian support, especially in the face of natural disasters. In addition, through her work, Prof. Diaz Gonzalez has researched several issues connected to the repercussions of the North American hegemony towards Cuba, tracing a new horizon of the new world leaderships in financial, political and diplomatic matters with a historical and analytical reference. She also discusses achievements and democratic challenges of the Cuban society as a sovereign and patriotic struggle, even against the mainstream beliefs on the matter.